RELEVANSI NILAI REVALUASI ASET TETAP DENGAN TINGKAT UTANG SEBAGAI VARIABEL MODERASI - Aryani, Fransisca Ayudya; Juliarto, Agung (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2017)
This study aims to analyze the value relevance of fixed asset revaluation and whether debt levels moderate value relevance of fixed asset revaluation. Signaling theory states that the company revalues its assets with the aim to provide credible signals about favorable future prospects; whereas debt contracting theory suggests that firms with high debt levels have opportunistic motives in doing the revaluation of fixed. This study uses 54 data of nonfinancial companies listed on the Indonesian Stock Exchange and have revalued its fixed assets in the period 2012-2015. The results shows that the revaluation of fixed asset has a value relevance, and leverage moderates this value relevance. Companies are trying to show the fair value of assets and an overview of the actual company's financial condition by revaluing their assets. However, when the company revalued its assets and has a fairly high leverage, investor respons negatively on revaluation conducted. Investors perceive that it is an opportunistic motives of managers to avoid the costs arising from the loan agreement.